(untitled) (Revista Rupturas, 2021)
In this text we talk and debate about the role of Digital Technologies in the present global situation. How the phenomenon of hypervirtualization has become the main way of producing and consuming artistic and cultural expressions. As well as its main aspects and tensions, both from the creators of these expressions, as well as from the consumption by the public.